Rethinking the study of nature a meta-epistemically view towards sustaining human life - Gianan, Nicolito A. (2008)
This account claims that the study of nature goes beyond mere knowing and understanding. It attempts to illustrate the fact that human life and its existence must be prioritized, for only the human can apply both knowledge and understanding to oneself, others, and the environment, including its component mechanisms. Hence, a meta-epistemic rethinking is vital, in which the idea of sustainability essentially points to the human as the responsible and accountable agent of promoting life, human life above all, and its continued existence in a healthy environment.
Keywords: Nature -- Effect of human beings on; Nature study